Diagnosis of Protein-Energy Deficiency: The Role of Total Protein and Transferrin in the Blood - Ashurova G. Z.; Satvaldieva E. A. (Scientific Trends, 2024)
The diagnosis of protein-energy deficiency, also known as protein-energy malnutrition (PEM), is a complex process that requires the evaluation of multiple biochemical and anthropometric parameters. Among these, total protein and transferrin in the blood play a crucial role in identifying individuals at risk of PEM. This article will discuss the significance of total protein and transferrin in the diagnosis of PEM, highlighting their physiological roles, laboratory measurements, and clinical implications.
Keywords: PEM, role, blood system, biochemical process, diagnoses, clinical measures.